Pengaruh Pembelajaran Kooperatif Tipe Jigsaw Terhadap Pengetahuan Dan Sikap Mahasiswa Dalam Manajemen Asfiksia Bayi Baru Lahir (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Student of Diploma III Midwifery is demanded to master new born asphyxia management. Student Centered Learning method as one of cooperative learning Jigsaw type has been verified to improve study achievement, to practice critical thinking, and to develop student’s social quotients.Objective: This researchhas an aim to analyze the influence of cooperative learning type Jigsaw on the improvementof student’s knowledge and attitude in studying new born asphyxia management.Method: Research design is quasi-experiment with control group. Data are taken from pre-test and post-test. Research instrument for knowledge uses multiple choice questions. Research instrument for attitude uses questionairewith Likert scale. Target population are students of Diploma III Midwifery semester III who aregetting new born asphyxia management materials. Sample are students of Diploma III Midwifery semester III who are getting new born asphyxia management materials at Health College A. Yani Yogyakarta. Techniquesampling usestotal sampling.Result: The result isthe knowledge of students who follow method of cooperative learning Jigsaw type improve to 63% (p